All the King’s Women: Polygyny and Politics in Europe, 900–1250 - Rüdiger, Jan, author.
1 online resource.
Keywords: Polygyny, in Europe? The grand narrative of Western history is the development of monogamous marriage, culminating in the central Middle Ages. Other kinds of relationships have often, perhaps too lightly, been dismissed as ‘just lust’. In this book, Jan Rüdiger investigates the plurality of man-woman relationships in medieval Scandinavia and analyses the social and political ‘uses’ of elite polygyny. By way of comparison the findings from the North are then applied to England, France, and the Iberian Peninsula, in order to propose a new overall image of elite polygyny, including marriage, in the medieval West.